A Rational Theory of the Size of Government - Meltzer, Allan H.; Richard, Scott F. (Journal of Political Economy, 1981)
In a general equilibrium model of a labor economy, the size of government, measured by the share of income redistributed, is determined by majority rule. Voters rationally anticipate the disincentive effects of taxation on the labor-leisure choices of their fellow citizens and take the effect into account when voting. The share of earned income redistributed depends on the voting rule and on the distribution of productivity in the economy. Under majority rule, the equilibrium tax share balances the budget and pays for the voters' choices. The principal reasons for increased size of government implied by the model are extensions of the franchise that change the position of the decisive voter in the income distribution and changes in relative productivity. An increase in mean income relative to the income of the decisive voter increases the size of government.